THE ACTIVITY OF 4-AMINOQUINOLINE AGAINST PLASMODIUM FALCIPARUM IN SOUTHERN IRAN - AV. Manouchehri; M.Motabar; A. Al Mohammad (Tehran University of Medical Sciences, 1973)
The resistance of Plasmodium falciparum to 4-amioquinolines has been confirmed in parts of South America such as Venezuela, Colombia, Brazil and Panama since 1961. During 1968-1970, 147 P. falciparum cases in the Kazeroon and Bandar Abbas areas were tested against 4-aminoquinolines, bases on 25 mg Resochin /kg of body weight over a period of 3 days. Twenty-foure, 48 , 72 and 96 hours after drug administration, the parasitemia rate was 80.5, 24.8, 1.65 and 0 per cennt, respectively . Blood samples taken from the subjects showed no asexual parasitemia for up to 28 days. Tests were carried out by the two - stage and single - stage methods (WHO, 1965 , 1967).The subjects were observed daily for 7 days after drug administration and then weekly for up to 4 weeks. Urine samples were taken and examined for chloroqine by days, one subject showed parasitemia. He was re-treated with 4-aminoquinolines and his blood was cleared of asexual parasites after the administration of 1500 mg of chloroqine.These studies showed that the local strain of P. falciparum in this area was susceptible to chloroqine.